2021
DOI: 10.1038/s41598-021-84446-9
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-level breakdown of Green–Kubo relations provides new insight into the mechanisms of thermal conduction

Abstract: Precise control of thermophysical properties of liquids through tailor-made design of the liquid molecular structure is a goal that, if achieved, could have significant positive impacts on machine design, performance and durability. In this work we show how the breakdown of the Green–Kubo relations down to the atomic level in molecular dynamics simulation can give useful insight into the mechanisms of thermal conduction. Using a group of five small alcohols as a case study, we demonstrate how combining this le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…which are linked to the kinetic of the molecular motion inside fluid itself, with these typically obtained using Green–Kubo relations. 50 52 …”
Section: Methods: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…which are linked to the kinetic of the molecular motion inside fluid itself, with these typically obtained using Green–Kubo relations. 50 52 …”
Section: Methods: State-of-the-artmentioning
confidence: 99%
“…Finally, it provides the frictional properties of the liquid (viscosities, conductivities, diffusion etc.) which are linked to the kinetic of the molecular motion inside fluid itself, with these typically obtained using Green–Kubo relations. …”
Section: Methods: State-of-the-artmentioning
confidence: 99%
“…The thermal or heat transport property of materials applied in nanotechnologies and other related application is of utmost importance. Varying theories have been used to explain the thermal conductivity of GFMs such as non-equilibrium MD (Galamba et al, 2007;Font et al, 2021), Green−Kubo formula with equilibrium MD (Manjunatha et al, 2021), Boltzmann transport equation (Tan et al, 2015;Jiang et al, 2017) and so on. Zhang et al (2012) studied the thermal conductivities (TC) of four GFMs and found that the presence of the acetylenic linkages in the GFMs caused excess reduction in their thermal conductivities due to the associated low atom density in the structures and weak single bonds.…”
Section: Thermal/thermoelectricmentioning
confidence: 99%
“…To calculate kinetic properties, MD uses time-dependent fluctuations to integrate correlation functions (see section ). With Green–Kubo relations, MD has been used to calculate transport properties such as diffusivity, thermal conductivity, and dynamical heterogeneities. − , MD also captures fluctuations in thermodynamic parameters such as enthalpy and volume, allowing these atomic simulations to calculate thermodynamic fluctuations using the methods discussed in section …”
Section: Modeling Techniquesmentioning
confidence: 99%